A República de Platão: uma investigação sobre o percurso da justiça no homem e na cidade - Souza, Wilder Silva de (2020)
This dissertation tries to accompany the concept of justice in Plato's work entitled The Republic. The research has as a starting point to analyze the questions presented in the dialogues of book I. It is intended to reconstruct and expose the arguments and answers offered by Plato to the initial problem of justice, in particular through his characters Cephalus, Polemarchus, Thrasymachus and Socrates about the concept and definition of justice. The initial discussion revolves around the definition presented by Thrasymachus and focuses, above all, on the concept of justice understood as the convenience of the stronger (338c) and of injustice as more advantageous than justice (343a-344c). It can be seen that Socrates' intention is to convince Thrasymachus that the unjust man cannot live better and be happier than the just man (353e). More than that: Socrates carries out an examination of the issue with Thrasymachus, as well as advances in the discussion with two other characters in the dialogue, Glaucon and Adeimantus. On the other hand, before the analysis focuses on the reconstruction and exposition of the arguments presented from book I of Plato's work dedicated to the theme, it is initially proposed to investigate some aspects of justice in pre-Platonic thought, starting with first educators of ancient Greece, the poets Homer and Hesiod, then passes by the legislator Solon, for the emergence of philosophy from some of the so-called pre-Socratic thinkers or philosophers of nature, such as Thales, Heraclitus and Pythagoras, as well how the flourishing of sophistry is investigated from some of the sophists, such as Protagoras, Thrasymachus, Hippias and Antiphon. It seeks to show the changes that the concept of justice has undergone. Next, it is a question of analyzing this concept in Plato's Republic, especially from the plot of book I of the work. We conclude that, for Plato, justice lacks a foundation, a universal and intelligible structure that, being truly good, must be sought in an objective reality, that is, in nature. For this reason, he considered the need to undertake an investigation about the existence of a norm or order linked to nature that, being strictly ordered and natural, must be learned in order to arrive at universal and immutable truths, especially with regard to the definition of justice. This means that reflection on the just city cannot dispense with an investigation into the virtuous soul.